PENGUKURAN TINGGI DAN DIAMETER TANAMAN MERANTI MERAH (Shorea pauciflora C.F. Gaertn) DI KEBUN RAYA UNMUL SAMARINDA (KRUS) - Herijanto Thamrin (Politeknik Pertanian Negeri Samarinda, 2020)
Forest is a natural resource that can be renewed and utilized. Utilization of forest resources must pay attention to the principle of being beneficial and providing sustainable results for humans. Forests must be maintained in order to get these benefits. The purpose of this study was to determine the height and diameter of the Red Meranti tree (Shorea pauciflora C.F. Gaertn) at the age of 13 at the Botanical Garden Unmul Samarinda (KRUS). The expected results of this study are to provide information on the height and diameter growth of red meranti (Shorea pauciflora.C.F.Gaertn). This research was conducted at the Kebun Raya Unmul Samarinda (KRUS) for 2 months, namely July - August 2020. Sampling was done with simple random sampling, on red meranti plants 13 years old with a spacing of 6 x 6 m as much as 50 trees. Measuring Diameter using Phiband and Height using a clinometer and a 4 m long pole tool. The results obtained were processed with simple statistics and analyzed using descriptive methods. Based on the results of the processing and data analysis carried out, it can be concluded that the diameter growth of the red meranti plant aged 13 years in the Botanical Garden of Unmul Samarinda (KRUS) did not vary (relatively uniform) with an average diameter of 13.42 cm, where the plant with a diameter large grow on the edge of the area and small ones are in the middle of the area. Meanwhile, the height growth of red meranti plants did not show any variation (relatively uniform) with an average height of 11.59 m. To get optimal results, both in height and diameter, plant maintenance activities are needed, especially cleaning existing weeds.